Tata Persuratan yang Efektif Dalam Organisasi Modern - Qatrunnada Jinan Akmaliah; Selvi Dewi Rahayu; Haenul Jarya; Iswanto (CV. ITTC INDONESIA, 2024)
Effective correspondence in modern organizations, where correspondence (archives) in modern times must follow technological developments. with technology, archives will make it easier to maintain internal organizational communication in modern times. considering the advantages and disadvantages of using technology, this can be a guideline for current organizations to develop correspondence. The method used in this study is a systematic review using qualitative methods. By using technology, correspondence (archiving) will be more effective because it will maintain the flow of organizational communication and make it easier to maintain organizational letters. Changes in the management of correspondence in the modern era today need to be seen not only in a technical context. Instead, the management of correspondence here should consider the user’s perspective the dynamics of behavior and the needs of all those involved, looking at the advantages and disadvantages of digital use. However, modern organizations today must also pay attention to the needs and changes that are specifically needed for themselves. Cooperation and collaboration can support success in continuing to process in anticipate changes in management.